Expression of apoptosis-related genes at different stages of BoHV-1 and 5 infection of bovine neural tissue - Martínez Cuesta, Lucía (2022)
Bovine alphaherpesviruses (BoHV) 1 and 5 share many genetic and structural characteristics; however, they differ in their ability to cause encephalitis. Previous research suggests that this difference might be caused by a differential modulation of apoptosis. In this study, we analyzed the mRNA expression of Bax, Bcl-2, Fas and caspases 3 and 8 in neural tissue sections of BoHV-1 and BoHV-5 experimentally-infected cattle. Overall, Fas and caspase 3 mRNA was up-regulated during BoHV-5 acute infection, latency, and reactivation. Conversely, caspase 3 mRNA levels increased only in the olfactory cortex during BoHV-1 acute infection, and it was down-regulated during reactivation, while Fas was only up-regulated during BoHV-1 acute infection and latency. Moreover, Bax/Bcl-2 ratio was lower than 1 during BoHV-1 acute infection except in the trigeminal ganglion, whereas many brain regions exhibit a ratio higher than 1 during BoHV-5 acute infection and reactivation. In summary, our findings suggest that during acute infection and reactivation, BoHV-5 induces a pro-apoptotic condition that could partially justify its increased ability to cause neurological damage.